Colonic Atresia due to Internal Herniation through the Falciform Ligament Defect: A Case Report - Varsha Soni; PRAKASH D. VALSE; Sameer Vyas (EL-Med-Pub, 2014)
Colonic atresia is the rarest outcome of all gastrointestinal type of internal hernia. We report a case of neonate with atresia of the transverse colon caused by herniation of the transverse colon through a defect in falciform-ligament.